PENGARUH JOB SATISFACTION, KOMPENSASI, DAN SUBJECTIVE WELL-BEING TERHADAP KINERJA - Marselia, Elsa Adela; Aryati, Ana Sofia (Jurnal Kewirausahaan dan Inovasi, 2023)
The goal of this quantitative explanatory research is to identify the effects of job satisfaction, compensation, and subjective well-being on teacher’s performance. This study was conducted at the Public Senior High School 2 of Amlapura using multiple linear regression analysis performed in SPSS 26 in order to explain the relationship between the three independent variable on the dependent variable. The stages in this study are instrument test, classical assumption test, and hypothesis testing. The instrument test consists of validity and reliability testing, while the classical assumption test consists of multicollinearity, heteroscedasticity, and linearity tests, and the hypothesis testing consists of F test and t test. The research population is teachers of Public Senior High School 2 of Amlapura; using saturated sampling, all 58 of them were selected as the respondents. The data was harvested through Likert-scaled questionnaires. This study finds that job satisfaction significantly influences the teacher’s performance, that compensation significantly affects the teacher’s performance, and that subjective well-being also significantly impacts the teacher’s performance.